2021
DOI: 10.1186/s13075-021-02504-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 induced senescence in intervertebral disc cells of patients with back pain can be attenuated by o-vanillin

Abstract: Background There is an increased level of senescent cells and toll-like teceptor-1, -2, -4, and -6 (TLR) expression in degenerating intervertebral discs (IVDs) from back pain patients. However, it is currently not known if the increase in expression of TLRs is related to the senescent cells or if it is a more general increase on all cells. It is also not known if TLR activation in IVD cells will induce cell senescence. Methods Cells from non-degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…Although several TLRs are detected in isolated human IVD cells, expression of TLR-1/2/3/4 and 6 was found to be dependent on degree of IDD [ 58 ]. Activation of human IVD cells with TLR-2/6 agonists for up to 48 h can induce senescence [ 59 ]. In addition, stimulation with the TLR-4 ligand lipopolysaccharide (LPS) for 24 h increases the expression of p16 INK4a and p21 to induce senescence in human NP cells from IDD patients [ 60 ].…”
Section: Disc Cell Senescence Under Various Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several TLRs are detected in isolated human IVD cells, expression of TLR-1/2/3/4 and 6 was found to be dependent on degree of IDD [ 58 ]. Activation of human IVD cells with TLR-2/6 agonists for up to 48 h can induce senescence [ 59 ]. In addition, stimulation with the TLR-4 ligand lipopolysaccharide (LPS) for 24 h increases the expression of p16 INK4a and p21 to induce senescence in human NP cells from IDD patients [ 60 ].…”
Section: Disc Cell Senescence Under Various Stressorsmentioning
confidence: 99%
“…Both compounds reduced inflammatory cytokines, chemokines, and growth and neutrophilic factors in pellet culture and in the intact human IVDs [ 167 ]. In addition, o-vanillin reduced the number of SnCs in cell pellet culture from degenerated discs and inhibited the TLR-2-induced senescence of disc cells isolated from patients with back pain and IVD degeneration [ 59 ]. Mechanistically, o-vanillin reduced TLR-2 and p16 INK4a co-expressing cells, suggesting that blockage of TLR-2 by o-vanillin reduces the detrimental effect of SnCs [ 59 ].…”
Section: Therapeuticsmentioning
confidence: 99%
“…COX‐2 upregulation and the overproduction of PGE 2 have also been observed in human nonalcoholic steatohepatitis‐associated liver cancer [15]. Moreover, TLR2 [47,49] and TLR4 [50] are also reportedly activated in senescent cells, indicating their potential involvement in the extrinsic control of SASP induction [50].…”
Section: Sasp Induction Mediated By the Innate Immune Responsementioning
confidence: 99%
“…The latest study has found that the grape seed extract PCC1 also has senolytic properties, which may be stronger than existing compounds ( Xu Q. et al, 2021 ). Among them, curcumin and its metabolite o-Vanillin have been proven to eliminate senescent cells in the intervertebral disc, reducing SASP secretion and alleviating IVDD ( Cherif et al, 2019 ; Mannarino et al, 2021 ). Our previous study has elucidated that quercetin could significantly reduce the proportion of senescent cells in the intervertebral disc through the Nrf-2/NF-κB pathway and slow down the deterioration of IVDD ( Shao et al, 2021 ).…”
Section: Senescent Cells Play An Indispensable Role In Intervertebral...mentioning
confidence: 99%